Effects of corn malt on rumen fermentation, blood metabolites and growth performance in fattening goats - Srakaew, Wuttikorn; Thongnum, Athichat; Bungsrisawat, Panatda; Bourapa, Ratchanee (Agriculture and Natural Resources, 2025)
Importance of the work: Corn malt (CM), derived from fermented corn grain, has the potential to improve ruminant feed quality and enhance growth. Objectives: To evaluate the effects of different CM and fermented corn husk (CH) ratios on rumen fermentation, blood metabolites and growth performance in fattening goats. Materials and Methods: In total, 20 male crossbred Native × Boer goats (13.0 ± 4.0 kg initial body weight) aged 3 mth were randomly assigned to five total mixed ratio (TMR) diets: T1 = 50% corn grain (CG) + 50% CH; T2 = 50% CM + 50% CH; T3 = 60% CM + 40% CH; T4 = 70% CM + 30% CH; and T5 = 80% CM + 20% CH. A completely randomized design was applied for the 90 d trial. The parameters measured were: rumen pH, volatile fatty acids (VFA), ammonia-nitrogen (NH3-N), blood urea nitrogen (BUN), blood glucose, insulin, body weight gain (BWG), average daily gain (ADG), feed conversion ratio (FCR) and feed intake (FI). Results: The rumen pH, VFA, NH3-N and BUN levels were within their optimal ranges across treatments. The CM-based diets (T2–T5) produced higher blood glucose levels (p < 0.01) than T1. Goats fed T5 produced the highest BWG (12.97 kg), ADF (0.21 kg/day) and FI (1.38 kg/day), representing a 75% increase in ADG over T1. FCR was similar across treatments; however, higher CM inclusion enhanced nutrient utilization and feed palatability. Main finding: The TMR diet with 80% CM and 20% CH (T5) significantly improved growth performance and feed efficiency, suggesting its potential as a cost-effective strategy for fattening goats. Further studies are needed to validate its use in other ruminant species and diverse environments.